Iron deficiency anemia in a woman’s life cycle and its impact - Irwinda, Rima (Indonesian Nutrition Association, 2024)
According to WHO, iron deficiency anemia is a condition where the body lacks iron, which is proven by signs of iron deficiency in the tissues and insufficient iron reserves in the body, accompanied by a decrease in hemoglobin levels of >2 standard deviations from the reference value in the same population. Iron deficiency anemia is one of the most common micronutrient deficiencies that occurs in a woman's life cycle due to menstruation (blood loss), pregnancy (needs for the mother and fetus), and bleeding during childbirth.aanemi